Use of superconducting magnetic energy storage device in a powersystem to permit delayed tripping - Ahmed, S. Shahnawaz; Bashar, S.; Chatterjee, A. K.; Salam, Mohammed Abdus; Ahmad, H. B. (2000)
Use of a superconducting magnetic energy storage (SMES) device in an electric power system can extend the time margin required for clearing a fault without any loss of stability of the synchronous generators in the system. Necessary mathematical model and computer simulation results have been presented. A wider time margin would be beneficial in many ways, such as precluding unwanted line tripping following temporary earth fault or transient swings, deferring costly replacement of the existing relays and breakers by the faster ones, and making a fair decision on tripping, taking into consideration a large volume of on-line data, constraints and complicated policies likely to be encountered in operating a power system under deregulation or a competitive market environment.